2003
DOI: 10.1016/s0885-3924(03)00148-9
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Concerns of Women with Ovarian Cancer

Abstract: This study describes the symptom experience of women with ovarian cancer. A body of data consisting of 21,806 letters, cards, and e-mails written by ovarian cancer patients was donated to the City of Hope investigators by the founder and editor of Conversations!: The International Newsletter for Those Fighting Ovarian Cancer. Using ethnographic qualitative research procedures, meaningful comments in the data were bracketed and coded within physical, psychological, social, and spiritual domains according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 15 publications
(20 reference statements)
4
60
0
2
Order By: Relevance
“…A patient-focused model of care in which patients and health care providers work as a team might help alleviate some of the current concerns about control. Lack of energy (or fatigue) has been reported by other researchers (e.g., Donovan & Ward, 2005;Ferrell, Smith, Cullinane, et al, 2003). Yet, there is enough accumulated evidence about fatigue and its management that health care providers should be offering patients suggestions to help them manage this symptom, especially …”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A patient-focused model of care in which patients and health care providers work as a team might help alleviate some of the current concerns about control. Lack of energy (or fatigue) has been reported by other researchers (e.g., Donovan & Ward, 2005;Ferrell, Smith, Cullinane, et al, 2003). Yet, there is enough accumulated evidence about fatigue and its management that health care providers should be offering patients suggestions to help them manage this symptom, especially …”
Section: Discussionmentioning
confidence: 93%
“…In an ethnographic study based on material obtained from seven years of correspondence among survivors of ovarian cancer and a support newsletter, Ferrell, Smith, Cullinane, and Melancon (2003) reported that the debilitating side effects of treatment were often worse than the disease itself. The most common symptom was pain, including peripheral neuropathy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety and depression have been reported [15][16][17][18][19][20]. Qualitative studies and quality of life studies have shown that significant distress, impairments in physical, vocational, social, familial and sexual functioning may also occur [6,15,17,[21][22][23][24][25][26][27][28][29]. A recent prospective longitudinal study measured psychological disorders, such as anxiety and depression, perceived social support, neuroticism and coping strategies to control unwanted thoughts in ovarian cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Onun hastası olmak gerçek bir onur". [45] Kadınlar, sağlık bakım vericilerinin becerili, hızlı ve uzmanca bakımlarının yanı sıra kanser tanısına baştan sona eşlik eden fiziksel ve duygusal "acı çekme" süreçlerinde yanlarında olmalarına gereksinim duymaktadırlar: "Bazen kötü hissedersin, sonra hemşireler yanına gelir ve seninle konuşur. Ve ne olduğunu anlayana kadar yanından ayrılmazlar".…”
Section: Tema 3 Yeni Bir Varoluşa Doğru…unclassified